Controlling Nanomaterial Size and Shape for Biomedical Applications via Polymerization‐Induced Self‐Assembly. Issue 2 (9th August 2018) - Khor, Song Yang; Quinn, John F.; Whittaker, Michael R.; Truong, Nghia P.; Davis, Thomas P.
Abstract: Rapid developments in the polymerization‐induced self‐assembly (PISA) technique have paved the way for the environmentally friendly production of nanoparticles with tunable size and shape for a diverse range of applications. In this feature article, the biomedical applications of PISA nanoparticles and the substantial progress made in controlling their size and shape are highlighted. In addition to early investigations into drug delivery, applications such as medical imaging, tissue culture, and blood cryopreservation are also described. Various parameters for controlling the morphology of PISA nanoparticles are discussed, including the degree of polymerization of the macro‐CTA and core‐forming polymers, the concentration of macro‐CTA and core‐forming monomers, the solid content of the final products, the solution pH, the thermoresponsitivity of the macro‐CTA, the macro‐CTA end group, and the initiator concentration. Finally, several limitations and challenges for the PISA technique that have been recently addressed, along with those that will require further efforts into the future, will be highlighted. Abstract : Polymerization‐induced self‐assembly (PISA) is a robust technique for obtaining concentrated solutions of polymeric nanoparticles with controlled sizes and shapes. This feature article provides readers with an update of the chemistry used to control the physicochemical properties of PISA nanoparticles and recent biomedical applications of these nanomaterials.